Rapid biomimetic remineralization of the demineralized enamel surface using nano-particles of amorphous calcium phosphate guided by chimaeric peptides. Issue 11 (November 2017) - Xiao, Zuohui; Que, Kehua; Wang, Haorong; An, Ran; Chen, Zhen; Qiu, Zhongjun; Lin, Mingli; Song, Jinhua; Yang, Jie; Lu, Danyang; Shen, Minjuan; Guan, Binbin; et al.
Abstract: Objective: The objective of this study was to develop a rapid and effective method to remineralize human carious-like enamel using chimaeric peptide-mediated nanocomplexes of carboxymethyl chitosan/amorphous calcium phosphate (CMC/ACP), mimicking the mineralizing pattern of the oriented assembly of ACP guided by amelogenin in the biomineralization of enamel. Methods: CMC/ACP nanocomplex solution was first synthesized through the successive addition of carboxymethyl chitosan, calcium chloride, and dipotassium phosphate into distilled water. ACP nanoparticles were degraded by 1% NaClO from CMC/ACP nanocomplexes. The morphology of the particles at different periods was tested by transmission electron microscopy (TEM). The chimaeric peptides were added to guide the arrangement of ACP nanoparticles and to bind ACP nanoparticles to the demineralized enamel surface specifically. X-ray diffraction (XRD)/scanning electron microscope (SEM)/confocal laser scanning microscopy (CLSM)/nano-indentation tests were applied to check the remineralization effects. Results: CMC/ACP nanocomplexes were obtained and could be kept without precipitation for a long time. After the degradation of NaClO and guidance of chimaeric peptides, ACP nanoparticles were arranged into oriented arrays before transforming into crystals, and the enamel-like crystals were tightly bound onto the demineralized surface. The newly formed enamel-like crystals were nearly well-organized and equipped with strong mechanical properties.